The Effect of Zinc Supplementation on Reducing Dengue-Related Morbidity in Pediatric Patients in Jakarta - Digambiro, Reza Aditya; Setyaningrum, Dyah Ayu Woro; Dewi, Intan Keumala; Ananingsih, Pangisti Dwi (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Dengue hemorrhagic fever is an endemic disease that causes significant morbidity, particularly in Jakarta. Based on previous studies, zinc has immunomodulatory properties that can function to improve the immune response to infections, including dengue. This study aims to evaluate the effectiveness of zinc supplementation in reducing morbidity and improving clinical conditions in pediatric patients with dengue hemorrhagic fever. Methods: This study utilized a prospective cohort method with a sample of 200 pediatric patients suffering from dengue hemorrhagic fever. The sample was divided into two groups: the intervention group (given zinc supplementation) and the control group (standard care without zinc supplementation). Laboratory assessments included serum zinc levels, severity of clinical symptoms, and hematological examination results. Results: The analysis showed a significant increase in serum zinc levels in the group given zinc supplementation, with the mean increasing from 100.34 ± 27.69 µg/dL to 104.28 ± 28.65 µg/dL on day 14 (p < 0.05). The number of patients whose clinical symptoms gradually became milder increased from 40% to 55% in the intervention group, whereas in the control group, there was a decrease in the number of patients with gradually milder symptoms, from 40% to 36%. Conclusion: Zinc supplementation is quite effective in reducing morbidity and improving clinical conditions in pediatric patients with dengue hemorrhagic fever.